2011
DOI: 10.1534/g3.111.001123
|View full text |Cite
|
Sign up to set email alerts
|

A Geographically Diverse Collection ofSchizosaccharomyces pombeIsolates Shows Limited Phenotypic Variation but Extensive Karyotypic Diversity

Abstract: The fission yeast Schizosaccharomyces pombe has been widely used to study eukaryotic cell biology, but almost all of this work has used derivatives of a single strain. We have studied 81 independent natural isolates and 3 designated laboratory strains of Schizosaccharomyces pombe. Schizosaccharomyces pombe varies significantly in size but shows only limited variation in proliferation in different environments compared with Saccharomyces cerevisiae. Nucleotide diversity, π, at a near neutral site, the central c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
106
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 36 publications
(47 reference statements)
7
106
0
Order By: Relevance
“…Despite being haploid, S. pombe undergoes an extended G 2 phase of the cell cycle, presenting an opportunity for unequal crossover between sister chromatids, a likely mechanism for such large duplications. We note that large duplications are commonly observed segregating in the S. pombe population (Brown et al 2011;Fawcett et al 2014).…”
Section: Insertion Bias Among Insertion-deletion Mutations (Indels)mentioning
confidence: 65%
See 2 more Smart Citations
“…Despite being haploid, S. pombe undergoes an extended G 2 phase of the cell cycle, presenting an opportunity for unequal crossover between sister chromatids, a likely mechanism for such large duplications. We note that large duplications are commonly observed segregating in the S. pombe population (Brown et al 2011;Fawcett et al 2014).…”
Section: Insertion Bias Among Insertion-deletion Mutations (Indels)mentioning
confidence: 65%
“…In the wild, S. pombe occurs in small, incompletely isolated populations with only weak population structure resulting from recent global dispersal (Brown et al 2011;Jeffares et al 2015). Beyond this, little is known of its natural ecology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 88 independent natural isolates of S. pombe showed that this fission yeast is karyotypically variable, and that one Japanese strain, CBS 2777, contains four chromosomes (8). In the present study, we determined the genome sequence and organization of CBS 2777 and found that it is related to the karyotype of the laboratory strains by a complex rearrangement.…”
mentioning
confidence: 56%
“…S6), suggesting that all four strains are mosaics that recently descended from a small pool of relatively diverse natural founder strains, as has been observed for Saccharomyces cerevisiae industrial isolates (13). The two other Japanese strains, CBS 2775 and 2776 (8), were isolated at the same time and in the same location as CBS 2777 and have the same genotype, but contain three chromosomes. The close relationships among these three strains also suggest that the chromosome rearrangement in CBS 2777 is of recent origin.…”
mentioning
confidence: 64%